Toxicity in man due to stain removers containing 1, 2-dichloropropane. Issue 11 (November 1985) - Pozzi, C; Marai, P; Ponti, R; Dell'Oro, C; Sala, C; Zedda, S; Locatelli, F
Abstract : There are reports that 1, 2-dichloropropane, a constituent of many commercial solvents and stain removers in Italy, has caused severe liver damage and, sometimes, acute renal failure. Between 1980 and 1983 three cases of 1, 2-dichloropropane intoxication (1 by ingestion, 2 by inhalation) were observed. Clinical features included severe liver damage, acute renal failure (2 patients), haemolytic anaemia, and disseminated intravascular coagulation. The most surprising features were haemolytic anaemia and disseminated intravascular coagulation which have not been reported before. The clinical picture was similar despite different modes of exposure.